The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1515/jpem-2019-0002
|View full text |Cite
|
Sign up to set email alerts
|

Association of lipid profile and BMI Z-score in southern Iranian children and adolescents

Abstract: Background Heart disease has been the leading cause of death for decades in the US population. Dyslipidemia is the most important risk factor for cardiovascular disease (CVD), and it often starts during childhood. Methods This cross-sectional study was performed in a growth assessment clinic in the city of Shiraz to determine the relation between body mass index (BMI) and dyslipidemia among children and teenagers aged 2–18 years. Nine hundred and eighty-nine children including 422 boys and 567 girls were sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 30 publications
0
6
0
1
Order By: Relevance
“…LDL, TC, TG, and HDL are commonly used clinical blood lipid indicators, among which the increase of LDL is highly correlated with obesity [23,24]. Other studies have shown that TC and TG can be used as independent risk factors for metabolic diseases such as obesity and may be used as indicators for early prediction of obesity in middle-aged and elderly people [25,26]. New study shows that HDL levels are inversely related to the incidence of cardiovascular events caused by obesity [23,27].…”
Section: Discussionmentioning
confidence: 99%
“…LDL, TC, TG, and HDL are commonly used clinical blood lipid indicators, among which the increase of LDL is highly correlated with obesity [23,24]. Other studies have shown that TC and TG can be used as independent risk factors for metabolic diseases such as obesity and may be used as indicators for early prediction of obesity in middle-aged and elderly people [25,26]. New study shows that HDL levels are inversely related to the incidence of cardiovascular events caused by obesity [23,27].…”
Section: Discussionmentioning
confidence: 99%
“…6,17 We also found that the prevalence of hypercholesterolemia and hyper-LDL-cholesterolemia in Korean boys and girls almost doubled and reached 9.4-12.4% and 8.0-9.7%, respectively, in 2016-2018. Although the age differences limit exact comparisons, this prevalence is much higher than the hyper-LDL-cholesterolemia prevalence of 2.4% in Japanese boys aged 13 years, 15 5.0-6.1% in Chinese adolescents, 16 6.4% in US adolescents, 6 and 6.5% in the Iranian pediatric population. 17,18 Our findings are consistent with a recent study showing a marked rise of hypercholesterolemia from 8.8% in 2007 to 18.0% in 2018 among Korean adults.…”
Section: Discussionmentioning
confidence: 78%
“…15 In China, where the prevalence of pediatric obesity has increased, all lipid profiles, including TC, LDL-C, HDL-C, and TG, showed adverse trends over the past decade. 16 In contrast, favorable trends in serum lipid profiles have recently been reported among the pediatric population in the US and Iran. 6,17 We also found that the prevalence of hypercholesterolemia and hyper-LDL-cholesterolemia in Korean boys and girls almost doubled and reached 9.4-12.4% and 8.0-9.7%, respectively, in 2016-2018.…”
Section: Discussionmentioning
confidence: 98%
“…The results of one study showed a steady increase in mean TC levels with increasing BMI, and this increase was statistically significant. The individual increases for boys and girls were also statistically significant [ 45 ]. According to Friedland et al, obese children with a BMI > 85% had significantly higher mean serum cholesterol and TG levels ( P < 0.05 ) [ 46 ].…”
Section: Discussionmentioning
confidence: 99%